Writers of the Black Chicago renaissance - Tracy, Steven C. (Steven Carl), 1954- (University of Illinois Press, 2011)
"This volume explores the contours and content of the Black Chicago Renaissance. A movement crafted in the crucible of rigid racial segregation in Chicago's "Black Belt" from the 1930s through the 1960s, its participants were also heavily influenced by--and influenced --the Harlem Renaissance and the Chicago Renaissance of white writers. Despite harsh segregation, black and white thinkers influenced one another particularly through their engagements with leftist organizations. In many ways, politically, racially, spatially, this was a movement invested in cross-pollination, change, and political activism, as much as literature, art, and aesthetics as it prepared the way for the literature of the Black Arts Movement and beyond. The volume begins with a look at Richard Wright, indisputably a central figure in the Black Chicago Renaissance with the publication of "Blueprint for Negro Writing." Wright sought to distance himself from what he considered to be the failures of the Harlem Renaissance, even as he built upon its aesthetic and cultural legacy. Subsequent chapters discuss Robert Abbott, William Attaway, Claude Barnett, Henry Blakely, Aldon Bland, Edward Bland, Arna Bontemps, Gwendolyn Brooks, Frank London Brown, Alice Browning, Dan Burley, Margaret Danner, Frank Marshall Davis, Katherine Dunham, Richard Durham, Lorraine Hansberry, Fenton Johnson, John Johnson, Marian Minus, Williard Motley, Marita Bonner, Gordon Parks, John Sengstacke, Margaret Walker, Theodore Ward, Frank Yerby, Black newspapers, the Chicago School of Sociologists, the Federal Theater Project, Black Music, and John Reed Clubs"--